2018
DOI: 10.1111/pops.12490
|View full text |Cite
|
Sign up to set email alerts
|

Partisanship, Political Knowledge, and the Dunning‐Kruger Effect

Abstract: A widely cited finding in social psychology holds that individuals with low levels of competence will judge themselves to be higher achieving than they really are. In the present study, I examine how the so-called "Dunning-Kruger effect" conditions citizens' perceptions of political knowledgeability. While low performers on a political knowledge task are expected to engage in overconfident self-placement and self-assessment when reflecting on their performance, I also expect the increased salience of partisan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 78 publications
2
53
0
4
Order By: Relevance
“…Teaching self-assessment is necessary to facilitate student self-efficacy and thus student retention. However, researchers have questioned the value of student self-assessment measures; the hypothesis that students who are least capable are those who are worst at self-assessment has dominated the literature (Mabe and West 1982;Falchikov and Boud 1989;Kruger and Dunning 1999;Dunning et al 2003;Dunning 2011;Ehrlinger et al 2008;Bell and Volckmann 2011;Dunning 2013, Ehrlinger andShain 2014;Webb and Karatjas 2018;Anson 2018). This belief has slowed efforts to teach student self-assessment and promote student metacognition.…”
Section: Self-assessment Self-efficacy and Self-regulationmentioning
confidence: 99%
“…Teaching self-assessment is necessary to facilitate student self-efficacy and thus student retention. However, researchers have questioned the value of student self-assessment measures; the hypothesis that students who are least capable are those who are worst at self-assessment has dominated the literature (Mabe and West 1982;Falchikov and Boud 1989;Kruger and Dunning 1999;Dunning et al 2003;Dunning 2011;Ehrlinger et al 2008;Bell and Volckmann 2011;Dunning 2013, Ehrlinger andShain 2014;Webb and Karatjas 2018;Anson 2018). This belief has slowed efforts to teach student self-assessment and promote student metacognition.…”
Section: Self-assessment Self-efficacy and Self-regulationmentioning
confidence: 99%
“…). Paradoxically, overconfidence stems in part from the observation that ‘ignorance is often invisible to those [who] suffer from it’ (Dunning : 250; see also Kruger & Dunning ; Anson ). Particularly when levels of knowledge are low, people tend to lack the meta‐cognitive awareness needed to recognise their deficits: they simply do not know they are missing relevant information and thus tend to overestimate their knowledge.…”
Section: Study 1: Manipulating Efficacymentioning
confidence: 99%
“…Now things have changed. Anson (2018) surveyed 2,606 American adults online as to their political knowledge. He found that those who performed worse were more likely to overestimate their performance.…”
Section: Populism and Political Knowledge In The Usmentioning
confidence: 99%
“…Moreover: When I asked partisans to "grade" political knowledge quizzes filled out by fictional members of the other party, low-skilled respondents gave out scores that reflected party biases much more than actual knowl-edge….More often than not, this means that partisans will think of themselves as far more politically knowledgeable than an out-partisan, even when that person is extremely politically knowledgeable. (Anson, 2018(Anson, , p. 1173 This was more the case among Republicans than Democrats, the former using partisan cues to judge peers' political knowledge to a greater extent confirming, Anson noted, the findings of an emerging literature on "asymmetric polarization" (Anson, 2018). To put it simply, the bulk of those identifying themselves as partisan Republicans, which by 2020 are effectively almost all supporters of Trump, are not only unaware of their being politically misinformed, but dismiss efforts to bring out the actual facts as politically motivated.…”
Section: Populism and Political Knowledge In The Usmentioning
confidence: 99%